Sarcoidosis: Epidemiology, Etiology, Pathogenesis, and Diagnosis - Setiawan, Fachri; Nurwidya, Fariz (Riviera Publishing, 2024)
Interstitial lung disease is a lung condition with wide variations. There are over 200 disorders classified under interstitial lung disease, including sarcoidosis. Sarcoidosis is a systemic disease characterized by the formation of non-caseating granulomas involving the lungs, lymphatic system, skin, and eyes. Clinical manifestations of sarcoidosis vary greatly, ranging from asymptomatic to severe symptoms with uncertain prognosis. The cause of sarcoidosis remains unknown, though several hypotheses suggest its association with genetic, environmental, infectious, and autoimmune factors. The main pathogenesis involves the formation of non-caseating granulomas involving various types of innate and adaptive immune cells. Based on its clinical presentation, sarcoidosis is classified into two types: Lofgren syndrome and non-Lofgren syndrome. Diagnosis of this disease can be established through clinical examination, radiological imaging, and biopsy revealing non-caseating granulomas. Corticosteroid therapy remains the primary treatment option, alongside immunosuppressive and biological therapies for advanced-stage sarcoidosis.